(untitled) (BIRDEM Medical Journal, 2017)
Background: Disorders of the musculoskeletal (MSK) system affect all ages and ethnic groups. This study was done to see the pattern of MSK disorders in diabetic and non-diabetic patients at a tertiary care hospital. Methods: This cross-sectional study was done between period of June 2016-Feb 2017 in the Department of Physical Medicine and Rehabilitation of a tertiary care hospital in Dhaka. Six hundred individuals were included in the study, 300 in diabetic and 300 in non-diabetic group. Results: Diabetic group consisted with 95 (31.67%) males, 205 (68.33%) females. Non-diabetic group consisted with 176 (58.67%) males and 124 (41.33%) females. Osteoarthritis knees (CoA of (101, 33.67%), degenerative lumber disc disease (69, 23%), frozen shoulder (60, 20%), degenerative cervical disc disease (42, 14%) and non-specific back pain (22, 7.3%), were common among diabetic patients. Among non- diabetic patients nonspecific back pain (55, 18.33%), degenerative lumbar disc disease (52, 17.33%), degenerative cervical disc disease (41, 13.66%), OA of knees (38, 12.60%), prolapsed lumbar inter- vertebral disc (PLID) (30, 10%) were common. Conclusion: Degenerative, non-inflammatory abnormalities comprised the major bulk of problems. Soft tissue rheumatism was common in diabetic patients. Frozen shoulder was present in higher percentage in diabetic patients. Birdem Med J 2018; 8(1): 68-71